A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam - Nguyen, Luan Thanh; Poyarkov, Nikolay A. Jr.; Nguyen, Tiep Tan; Nguyen, Tam Ai; Tran, Vy Huu; Gorin, Vladislav A.; Murphy, Robert W.; Nguyen, Sang Ngoc (Zootaxa, 2019)
We describe a new species of Microhyla from Tram Lap forest, Gia Lai Province, Central Vietnam based on morphological, molecular, and acoustic data. The new species resembles M. butleri morphologically, but differs from all congeners by a combination of the following morphological attributes: (1) medium-sized adult snout–vent length 25.2–27.0 mm in 15 males and 30.5 mm in a single female; (2) body habitus moderately stocky; (3) head flat, snout rounded, slightly prominent in ventral profile; (4) dorsum and flanks slightly shagreened with evenly scattered tiny tubercles, ventral skin smooth; (5) first finger well developed, more than one-half the length of the second finger; (6) tips of three outer fingers slightly enlarged, forming weak disks and tips of all toes distinctly dilated into wide disks with narrow peripheral grooves; (7) finger and toe disks with dorsal median longitudinal grooves; (8) three palmar tubercles and two metatarsal tubercles; (9) tibiotarsal articulation of adpressed limb reaching slightly beyond the orbit; (10) webbing formula: I 1¾–2 II 1½–2¾ III 2–31/3 IV 3¼–1½ V; (11) in life, chin and throat yellowish to bright-orange with tiny dark brown speckling laterally; and (12) a call consisting of 15–26 pulses with a dominant frequency of 1.8–2.2 kHz (recorded at 18.5ºC). We also provide a preliminary genealogy of Microhyla based on analysis of a 2644 bp fragment of 12S–16S rRNA mitochondrial DNA. Based on the examed data, the new species and M. butleri are sister-species (genetic p-distance: 9.0%) and it can be distinguished from M. butleri by its morphology (size, webbing on toes, color) and advertisement call. Interspecific genetic p-distances between the new species and its congeners vary from 9.0% to 14.8%. Microhyla aurantiventris sp. nov. occurs in evergreen montane tropical forests at elevations around 1200 m a.s.l. and is known only from the type locality. The new species appears to be threatened due to intensive logging and agriculture plantation.